Feeding strategies differentiate four detritivorous curimatids in the Amazon - Farago, Thatyla; Borba, Gabriel Costa; Amadio, Sidineia Aparecida; Oliveira, Joicyeny; Santos, Geraldo; Val, Adalberto Luis; Ferreira, Efrem J.G. (Web Ecology, 2020)
Differences in food intake and morphological attributes may facilitate the coexistence of detritivorous fish. The present study investigated the possible differences in the feeding strategies of four species of curimatids that inhabit the floodplain of the central Amazon. For this, we determined the diet, daily food cycle, and whether characteristics of the intestine were related to the length of the fish and the amount of detritus consumed. The detritivory was confirmed, and we observed a difference in the foraging time between species. We found differences in the length and weight of the intestine and the relationship of these variables with the length of the fish and the amount of detritus consumed. Our study suggests that despite belonging to the same family and food group, curimatids have characteristics that allow them to consume the detritus in different ways. © Author(s) 2020. This work is distributed under the Creative Commons Attribution 4.0 License.
Keywords: Coexistence; Detritivory; Feeding Behavior; Fish; Floodplain; Food Intake; Freshwater Ecosystem; Morphology; Amazon River; Curimatidae